Unraveling the Maintenance of Southeast Asia’s Maritime Security: A Look into the ASEAN Maritime Outlook - Abel Josafat Manullang (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
The sea is an important engine of development for the growth of Southeast Asia. It has provided the states with new opportunities for growth and development. It is not surprising that many initiatives have been undertaken to leverage the vast sea in the region. Under Indonesia’s chairmanship, ASEAN’s focus towards the maritime domain was accentuated by the release of the ASEAN Maritime Outlook (AMO). This new addition to ASEAN’s maritime security instruments serves as a reference for upcoming endeavors on the field and to avoid duplication. Through using the qualitative research methods, the author seeks to explore the ways ASEAN has sought to maintain its multifaceted maritime security. Against that backdrop, apart from elaborating what the AMO has to offer, the author also unravels the strides ASEAN has taken in maintaining some dimensions to its maritime security. The aforementioned dimensions, referring to Christian Bueger, consisted of national security, human security, marine environment, and economic development. It is found how ASEAN’s effort to maintain maritime security is apparent in the initiatives done within its 3 pillars. Moreover, ASEAN also expands its effort by cooperating with actors outside of Southeast Asia in many aspects given the interconnectedness inherent to the sea. Based on the conclusion, it is recommended that ASEAN continues to prioritize and enhance its multifaceted approach to maritime security, building on the foundations laid by the ASEAN Maritime Outlook (AMO). ASEAN should intensify efforts to strengthen national security, human security, marine environment protection, and economic development through its three pillars: Political-Security Community, Economic Community, and Socio-Cultural Community. To further bolster these initiatives, ASEAN should deepen its cooperation with external partners, leveraging the interconnected nature of the maritime domain.